O holy night : Christmas with the Boys Choir of Harlem - Ringgold, Faith (HarperCollins/Amistad, 2004)
Presents the Christmas story according to Luke plus the words to five popular Christmas carols: Silent Night -- O Come All Ye Faithful -- O Holy Night -- Hark! the Herald Angels Sing -- and Joy to the World, sung on the accompanying CD by the Boys Choir of Harlem.